Business beyond the box - "O'Keeffe, John" (London, 1998)
'What can I do now to achieve breakthrough results in my business area?' Faster rates of change in the business world and in the world around us mean that we need to get 'out of our boxes' just to adapt productively to the changes taking place, let alone to develop a competitive edge for the future. Business Beyond the Box is about developing the ability to create a flow of ideas that will bring about a step-change in actual results. Your mind is a brilliant personal cranial computer which most of us don't know how to operate. The only thinking strategy most of us know is logical analysis; and the only alternative strategy we know is a vague form of brainstorming, which rarely delivers. Business Beyond the Box is about applying your mind to eight thinking strategies which work, based on a new concept called triangular thinking. Linear or vertical thinking was always close to tunnel vision. Then came lateral thinking, which brought a breadth of thought, but often ended up with ideas too impractical for business. Triangular thinking solves these limitations by being directly focused on bottom-line business results. It involves doing three things together: picturing a step-change, building knowhow, and using creative thinking - all focused on achieving breakthrough, real-world results. This is a breakthroughbook because the strategies it outlines are surprisingly effective at getting breakthrough results from relatively easy changes. Business Beyond the Box will give you the secrets of breaking through the box of incrementalism, of the self-imposed limitations you hardly realise are there, and applying new mindsets to achieve breakthrough results. This book will improve you and your organization's ability to innovate rather than administrate; to look at what can be rather than what is; to work with boundaries rather than work within boundaries.
Keywords: Mind